2016
DOI: 10.1103/physrevb.93.035129
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of excitonic magnetism in Ir double perovskites

Abstract: We combine several numerical and semi-analytical methods to study the 5d double perovskites Sr2YIrO6 and Ba2YIrO6 which were recently proposed to exhibit excitonic magnetism. Starting from the density functional theory and constrained random phase approximation we construct effective multi-band Hubbard models. These are analyzed by means of static and dynamical mean-field theories and strong coupling expansion. We find both materials to be insulators, but, contrary to the experimental claims, with a large spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 24 publications
4
50
1
Order By: Relevance
“…Our experimental results on single crystal XRD are in good agreement with the theoretical paper reported by Pajskr et al [22], which claims that the noncubic crystal field of Sr 2 YIrO 6 is found to be rather weak and that this compound is quite similar in terms of structure and low-energy properties to the cubic Ba 2 YIrO 6 analog [35].…”
Section: Resultssupporting
confidence: 82%
“…Our experimental results on single crystal XRD are in good agreement with the theoretical paper reported by Pajskr et al [22], which claims that the noncubic crystal field of Sr 2 YIrO 6 is found to be rather weak and that this compound is quite similar in terms of structure and low-energy properties to the cubic Ba 2 YIrO 6 analog [35].…”
Section: Resultssupporting
confidence: 82%
“…It is of interest that the simple electronic structure calculations employed here, in which only a basic electronic model have been applied, yield moments that are consistent with the experimental observations. We expect that recent, much more sophisticated calculations [29] will yield more detailed insight into the electronic and magnetic behavior of this system.…”
Section: Resultsmentioning
confidence: 99%
“…al. 5 rebutted this claim using dynamical mean field theory (DMFT) to obtain a non-magnetic ground state. Furthermore, this study estimated the gap between the J = 0 singlets and the J = 1 triplets to be more than 250 meV which marginalizes the prospect of condensation.…”
Section: 10mentioning
confidence: 99%